State of the nation: in the context of India's constitution - Nariman, Fali S. (New Delhi, 2013)
In this timely volume, the author's main focus is on the mother-of- all-problems': the tidal wave of corruption that has engulfed virtually all institutions of the state and almost all aspects of governance and administration across the country.
Keywords: India-Politics and governance